Effect of Internal Recycle Ratio on the Nutrient Removal Efficiency Using Enhanced Bardenpho Process - Masood M. Hazzaa; Waleed M. Alabdraba (Tikrit Journal of Engineering Sciences)
An appropriate recycling ratio can be determined to support the needed conditions for optimization operation in wastewater treatment. This study aims to address the impact of the Internal Recycle Ratio (IR) on Nutrient removal efficiency using an enhanced Bardenpho process. The reactors (Anaerobic, First Anoxic, First Aerobic, Second Anoxic, Second Aerobic) were constructed with a secondary settling tank to settle the biomass before discharge to accomplish significant nitrogen and phosphorus removal. After oxidizing in the second aeration chamber, the nitrate was recycled into the first anoxic chamber (IR1), first aerobic chamber (IR2), and second anoxic chamber (IR3). In that order, the internal recycle ratios of 0%, 100%, 200%, and 300% were shown to impact the biological removal of nitrogen and phosphorus using the Bardenpho process in the pilot-size plant. Input COD, TN, and PO4 values in raw synthetic wastewater of 413 mg/L, 35 mg/L, and 15 mg/L, respectively, were used to operate each IR. The IR of (200%) and IR1 attended maximum TN and PO4 removal efficiency of (92.86%) and (86.67%), respectively. IR of (0%) attended its maximum TN and PO4 removal efficiency at (51.4%) and (46.7%) respectively.